(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Epidural anaesthesia is widely used for lower limb orthopaedic surgeries because of its ability to provide effective intraoperative anaesthesia and prolonged postoperative analgesia. Addition of adjuvants such as dexmedetomidine, clonidine, and fentanyl to epidural local anaesthetics improves block characteristics and haemodynamic stability. This study was conducted to compare the effects of dexmedetomidine, clonidine, and fentanyl on intraoperative haemodynamics when used as adjuvants to epidural ropivacaine. Methodology: This randomized prospective comparative study was conducted in the Department of Anaesthesiology, Sree Mookambika Institute of Medical Sciences, Kulasekharam, from February 2025 to November 2025. A total of 45 ASA grade I and II patients aged 20–60 years undergoing lower limb orthopaedic surgeries under epidural anaesthesia were randomly divided into three groups of 15 each. Group A received ropivacaine with dexmedetomidine, Group B received ropivacaine with clonidine, and Group C received ropivacaine with fentanyl. Intraoperative haemodynamic parameters, onset and duration of sensory and motor blockade, analgesia, and adverse effects were assessed. Results: A statistically significant fall in systolic, diastolic, and mean arterial pressure was observed in Groups B and C from 15 to 120 minutes after epidural block (p<0.05). Dexmedetomidine demonstrated better haemodynamic stability compared to clonidine and fentanyl groups. All three groups provided effective anaesthesia and satisfactory analgesia with manageable adverse effects. Conclusion: Dexmedetomidine, clonidine, and fentanyl are effective epidural adjuvants in lower limb orthopaedic surgeries. Dexmedetomidine showed superior haemodynamic stability and prolonged analgesic effect with minimal adverse effects.